PESAN-PESAN KOMUNIKASI DAKWAH DALAM PETATAH-PETITIH MINANG - Umar Abdur Rahim (Sosial Budaya, 2017)
This paper focuses on the study of messages preaching communication that exist in cultural communication in Minangkabau society. About how the tradition of communication culture that exist in Minangkabau society is known as petatih-petitih, carrying messages of communication containing messages of da'wah in accordance with the teachings of Islam. The approach in this study uses a literature review approach, by studying, collecting and analyzing data sourced from several relevant, supportive literature, books and resources. The results show that the messages of communication that exist in Minangkabau society actually have relevance with messages of da'wah communication which contains messages of Islamic teachings that are sourced and refer to Al-qur'an and Hadith. In addition, petitih-petitih also has a very important role as a cultural communication that became a reference and became the handle of the life of Minangkabau society. Petitih is a form of oral communication in the form of a cultural proverb containing the counsels of parents passed down from generation to generation. So through the petitih-petitih loaded with Islamic values is created Minangkabau society is famous for the community that is identical to his religious values with the famous cultural culinary "customary basara syara 'syara basandi kitabullah".